A novel of bioprospecting of earthworm cast associated actinobacteria for its antimicrobial properties–Short communication - Gopikrishnan, V.; Radhakrishnan, M.; Joseph, J.; Abirami, B.; Manigundan, K.; Suresh, A.; Soytong, K. (International Journal of Agricultural Technology, 2021)
Among bacteria, the actinobacteria are the most significant source of bioactive compounds and many industrially important by products in use today. The present study designed to isolate the actinobacteria from earthworm cast for its antimicrobial properties. Totally 56 actinobacterial colonies were isolated from earthworm cast of Kanchipuram agricultural area. Of which, 36 morphologically different colonies were isolated and identified which mostly belong to Streptomyces. In antimicrobial activity, among 36 isolates, 12 were showed antimicrobial activity against one or more tested human pathogens eg Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. So, the study revealed earthworm cast associated actinobacteria can be recorded as an imperative resource for bio-prospecting that could produce novel bioactive metabolites